All Amorphous Oxide Bipolar Heterojunction Diodes from Abundant Metals. (15th January 2015) - Schlupp, Peter; Schein, Friedrich‐Leonhard; von Wenckstern, Holger; Grundmann, Marius
Abstract : Fully amorphous pn‐heterodiodes consisting of n ‐type zinc‐tin oxide and p‐type zinc‐cobalt oxide are discussed. All fabrication steps are conducted at room‐temperature except two baking steps within the photolithography for 90 s at 90 °C. Rectifications as high as six orders of magnitude are achieved and the ideality factors are between 1.2 and 2, depending on the diode design.